2021
DOI: 10.1111/jocd.14628
|View full text |Cite
|
Sign up to set email alerts
|

Use of quantum molecular resonance energy for managing postrhinoseptoplasty perilesional edema and ecchymosis

Abstract: Background Quantum molecular resonance (QMR) technology employs nonionizing high‐frequency waves ranging from 4 to 64 MHz to generate low‐intensity quanta of energy that interacts with cellular components. Aims To evaluate the efficacy and safety of QMR treatment on postoperative perilesional edema and ecchymosis in patients with rhinoseptoplasty or revision rhinoseptoplasty. Patients/Methods In total, 30 patients were treated with QMR stimulation therapy (QMR group) once daily for 5 days, while another 30 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It has been shown to positively affect wound healing and postoperative inflammation. 5,[10][11][12][13] QMR has been examined before in the context of DED. One previous study reported the capabilities of QMR in 27 patients with DED.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to positively affect wound healing and postoperative inflammation. 5,[10][11][12][13] QMR has been examined before in the context of DED. One previous study reported the capabilities of QMR in 27 patients with DED.…”
Section: Discussionmentioning
confidence: 99%
“…To the editor, This is the first case series to describe quantum molecular resonance (QMR) treatment can be effective in treating striae distensae (SD). 3 We speculate that the expression of markers to diminish inflammation and enhancement of growth factors such as VEGF impacting cellular regeneration could have influenced the production of new collagen and elastin, which helps to tighten the skin, resulting in increased firmness.…”
Section: Improvement Of Skin Firmness and Reduction Of Striae Distens...mentioning
confidence: 97%
“…QMR has been used to reduce inflammation and was used to treat edema in rhinoseptoplasty patients. 4 QMR improved meibomian gland expressibility and normalized inflammation markers by reduction of MMP-9. 5 We speculate that the improvement of mild acne may be due to downregulation of inflammation markers and the inhibition of inflammatory responses induced by QMR.…”
mentioning
confidence: 95%